The Paris affair - Marshall, Maureen (Grand Central Publishing, 2024)
"Fin Tighe is clinging to respectability by his nail-bitten fingers. He may be the illegitimate son of an English earl, but he hasn't spoken to his father in a decade, and his engineer's salary is barely enough to support him and his cousin Aurelie. A dancer in the corps de ballet, Aurelie is at constant risk from groping, leering men who assume any dancer is a prostitute in training. And Fin's evenings spent in the clandestine gay community may be legal through a loophole in the Napoleonic Code, but they leave him vulnerable. So, when Fin's employer, Gustave Eiffel, announces that he needs additional investors to pay for his pet project, a 300-meter tower that will dominate the city's skyline, Fin jumps at the chance. If he raises enough money, the commission will earn him a fortune, and hopefully, some protection. Capricious stranger Gilbert Duhais appears to be a boon from the gods. Gilbert is handsome, wealthy, connected, and somehow privy to Fin's background. Gilbert persuades Fin to masquerade as his father's heir-which couldn't be further from the truth-and introduces him to every nouveau riche speculator in the city. Each provocative interaction heightens Fin's risk of exposure. But also brings Fin closer to his dream of financial security. When a dear friend of Fin's is murdered above a clandestine gay club, the stakes rise even higher. Fin must untangle the disparate threads of his past-and his current romantic gamble-before they become his noose"--